Arterial Stiffness and Subclinical Myocardial Dysfunction in Pediatric Asthma: A Novel Approach Using Aortic Propagation Velocity - Rahmi Özdemir (Journal of Behçet Uz Children's Hospital, 2023)
Objective: Childhood asthma is associated with systemic inflammation, airway inflammation, and cardiac adverse effects such as right ventricular (RV) failure and pulmonary hypertension. Arterial stiffness, an early marker of atherosclerosis, can be assessed using the color M-mode-derived aortic propagation velocity (APV) method. This study aims both to evaluate APV as a measure of arterial stiffness and also subclinical myocardial dysfunction using Doppler echocardiography in children with asthma. Method: This prospective study evaluated early markers of arterial stiffness and subclinical myocardial dysfunction in children with asthma compared to a control group. The study included 44 children with asthma and 40 healthy controls. Echocardiographic measurements, including tissue Doppler imaging and color M-mode-derived APV were performed to assess ventricular function and arterial stiffness. Pulmonary function tests were also conducted for asthmatic patients. Results: Our study did not reveal any significant differences in APV, left ventricular function, mitral valve Em/Am ratios, and left heart myocardial performance indices between the asthma group and the control group. However, we observed a significant difference in the peak systolic velocity at the anterior leaflet of the tricuspid valve (tricuspid valve Em velocity), which suggests that diastolic function of the RV performance is impaired in children with asthma. Conclusion: This study is the first to evaluate APV in young children with asthma and has found no significant correlation between asthma and arterial stiffness or subclinical atherosclerosis. However, it has revealed that children with asthma are more likely to have RV diastolic dysfunction. Further studies are needed to investigate the potential link between childhood asthma and subclinical atherosclerosis.